The incidence of psychoses in diverse settings, INTREPID (2): a feasibility study in India, Nigeria, and Trinidad (2016)
Background. There are striking global inequities in our knowledge of the incidence, aetiology, and outcome of psychotic disorders. For example, only around 10% of research on incidence of psychotic disorders originates in low- and middle-income countries. We established INTREPID I to develop, implement, and evaluate, in sites in India (Chengalpet), Nigeria (Ibadan), and Trinidad (Tunapuna-Piarco), methods for identifying and recruiting untreated cases of psychosis, as a basis for investigating incidence and, subsequently, risk factors, phenomenology, and outcome. In this paper, we compare case characteristics and incidence rates across the sites. Method. In each site, to identify untreated cases of psychoses in defined catchment areas, we established case detection systems comprising mental health services, traditional and spiritual healers, and key informants. Results. Rates of all untreated psychoses were 45.9 (per 100000 person-years) in Chengalpet, 31.2 in Ibadan, and 36.9 in Tunapuna-Piarco. Duration of psychosis prior to detection was substantially longer in Chengalpet (median 232 weeks) than in Ibadan (median 13 weeks) and Tunapuna-Piarco (median 38 weeks). When analyses were restricted to cases with a short duration (i.e. onset within preceding 2 years) only, rates were 15.5 in Chengalpet, 29.1 in Ibadan, and 26.5 in Tunapuna-Piarco. Further, there was evidence of age and sex differences across sites, with an older average age of onset in Chengalpet and higher rates among women in Ibadan. Conclusion. Our findings suggest there may be differences in rates of psychoses and in the clinical and demographic profiles of cases across economically and socially distinct settings.